Social media influencer marketing: science mapping of the present and future trends - Fauzi, Muhammad Ashraf; Ali, Zuraina; Satari, Zanariah; Megat Ramli, Puteri Azlian; Omer, Mazen (Emerald Publishing Limited, 2024)
Purpose – This study aims to reveal the knowledge structure of social media influencer marketing literature by performing science mapping analysis through a state-of-the-art bibliometric approach to determine the current and future trends. Social media influencer marketing is one of the most effective approaches to presenting a brand and offering value to consumers via social media. Design/methodology/approach – This study evaluates the knowledge structure to uncover the emerging trends and future predictions in social media influencer marketing through bibliographic coupling and co-word analysis. In total, 917 journal publications were retrieved from the Web of Science database and analyzed using VOSviewer software. Findings – The central theme in social media influencer marketing reflects digital engagement between influencers and followers and communication between influencers and followers. The theoretical and managerial implications are discussed. Originality/value – This study unleashes the knowledge structure according to the fundamental literature of social media influencer marketing and the underlying themes related to the phenomenon